Clinical decision making in small non-functioning VHL-related incidentalomas. Issue 8 (August 2020) - Därr, Roland; Kater, Jonas; Sekula, Peggy; Bausch, Birke; Krauss, Tobias; Bode, Christoph; Walz, Gerd; Neumann, Hartmut P; Zschiedrich, Stefan
Abstract : The optimal treatment strategy for patients with small non-functioning VHL-related incidentalomas is unclear. We searched the Freiburg VHL registry for patients with radiologic evidence of pheochromocytoma/paraganglioma (PHEO/PGL). In total, 176 patients with single, multiple, and recurrent tumours were identified (1.84 tumours/patient, range 1–8). Mean age at diagnosis was 32 ± 16 years. Seventy-four percent of tumours were localised to the adrenals. Mean tumour diameter was 2.42 ± 2.27 cm, 46% were <1.5 cm. 24% of tumours were biochemically inactive. Inactive tumours were significantly smaller than active PHEO/PGL at diagnosis (4.16 ± 2.80 cm vs 1.43 ± 0.45 cm; P < 0.025) and before surgery (4.89 ± 3.47 cm vs 1.36 ± 0.43 cm; P < 0.02). Disease was stable in 67% of 21 patients with evaluable tumours ≤1.5 cm according to RECIST and progressed in 7. Time till surgery in these patients was 29.5 ± 20.0 months. A total of 155 patients underwent surgery. PHEO/PGL was histologically excluded in 4 and proven in 151. Of these, one had additional metastatic disease, one harboured another tumour of a different type, and in 2 a second surgery for suspected disease recurrence did not confirm PHEO/PGL. Logistic regression analysis revealed 50% probability for a positive/negative biochemical test result at 1.8 cm tumour diameter. Values of a novel symptom score were positively correlated with tumour size (Rs  = 0.46, P < 0.0001) and together with a positive biochemistry a linear size predictor ( P < 0.01). Results support standardised clinical assessment and measurement of tumour size and metanephrines in VHL patients with non-functioning incidentalomas <1.5 cm at one year following diagnosis and at individualised intervals thereafter depending on evolving growth dynamics, secretory activity and symptomatology.